A Methodological Proposal to Build Composite Indicators of Gender Equality. The Case of Rural Areas in Castilla y León - Rico, Margarita; Gómez-Limón, José Antonio (Revista Internacional de Sociología, 2011)
The socioeconomic unequality between genders is a multidimensional problem difﬁcult to be quantiﬁed as a whole. The use of composite indicators can help in this task by summarizing and interpreting the complete set of available information. Furthermore, these indexes can be used to analysis the disparities in the situation of women and men from a static point of view and also from a dynamic perspective. The usefulness of these composite indicators is even more important for the study of gender gap in rural areas, given the particular difﬁculties faced by women living in these districts. In this sense, the objective of this paper is to develop a methodology to build composite indicators of gender equity that quantiﬁes the existence of asymmetry between men and women in different kind of habitats. In order to validate the methodological approach proposed, this has been implemented for the Autonomous Region of Castilla y León (Spain). This case study is focused in the calculation of composite indicators that allow the comparison of gender gaps in rural, intermediate and urban areas.